Pliny the younger’s Letters as a source to study the roman uillae (Circe de clásicos y modernos, 2018)
Through this work we’ll try to prove the considerable value of Pliny the Younger’s letters as a source of conceptual and architec-tonical knowledge of roman uillae byanalyzing carefully their Epistolae and by proving too their archaeological reality not only in Italian uillae, but also in some Spanish ones recently recovered, specially in Andalusia, current region which roughly corresponds with the ancient Roman province of the Baetica.
Keywords: Pliny the Younger; Epistolae; uillae; Italy; Andalusia